2017
DOI: 10.3892/ol.2017.6028
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of circulating microRNAs as a predictive biomarker for the diagnosis and recurrence of papillary thyroid carcinoma

Abstract: Circulating microRNAs (miRNAs/miRs) are considered to be potential biomarkers for numerous types of cancer. However, previous investigations into the expression of miRNAs in the serum of patients with papillary thyroid carcinoma (PTC) to predict diagnosis, prognosis and recurrence have reported conflicting results, and the role of miRNAs remains unclear. The present study dynamically assessed the circulating miRNA profile in patients with PTC and determined whether miRNAs in the serum could be used as biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 70 publications
1
62
0
Order By: Relevance
“…In addition, similar to previous reports (18,45,(66)(67)(68) our results indicated that the expression levels of miR-222 and miR-221 are significantly increased in serum from III/IV stage PTMC cases. A previous study suggested that both miR-222 and miR-221 are clustered on the X chromosome, and it is likely that they are encoded by a single polycistron, as was previously suggested (69).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, similar to previous reports (18,45,(66)(67)(68) our results indicated that the expression levels of miR-222 and miR-221 are significantly increased in serum from III/IV stage PTMC cases. A previous study suggested that both miR-222 and miR-221 are clustered on the X chromosome, and it is likely that they are encoded by a single polycistron, as was previously suggested (69).…”
Section: Discussionsupporting
confidence: 92%
“…miRNAs can be isolated from serum or plasma, and they can be used to detect many types of cancers (39)(40)(41). However, the promising use of miRNAs as biomarkers for PTC has been reported in only a few studies (28,35,(42)(43)(44)(45). To date, no studies have examined circulating miRNA expression in PTMC patients, and none have attempted to use serum miRNAs to analyze their association with the clinicopathologic features of PTMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several countries were included in the 9 included articles: 7 focused China, one each from Korea 12 and Iran 13 . Seven articles used benign thyroid nodule (BTN) patients as controls, and two articles 14,15 using both BTN patients and healthy people as controls. One article 16 studied papillary thyroid micro carcinoma (PTMC) patients, and other eight articles studied PTC patients.…”
Section: Resultsmentioning
confidence: 99%
“…9 ), preoperative thyroglobulin antibodies as potential marker for PTC in patients with indeterminate thyroid nodules 10 , serum SERPINE2/Protease Nexin-1 and Secretory Leukocyte Protease Inhibitor (SLPI) concentrations as preoperative PTC biomarkers 11 , circulating miRNAs as a non-invasive biomarker for the diagnosis of PTC (ref. 12 ) and preoperative serum thyroglobulin (Tg) and changes in serum Tg during thyroid stimulating hormone (TSH) suppression as independent predictors of FTC in thyroid nodules with a cytological diagnosis of follicular lesion 13 . Nevertheless, continuous search for specific growth factors involved in the pathogenesis and progression of differentiated and anaplastic thyroid cancers still remains of utmost importance for improving preoperative diagnostics and for designing new therapeutic approaches to dealing with TC.…”
Section: Introductionmentioning
confidence: 99%